FOSTERING SUSTAINABLE INVESTMENT THROUGH GREEN SUKUK: THE MODERATING ROLE OF GOVERNANCE QUALITY IN OIC COUNTRIES - Abdul Qoyum; Nor Nabilla Muhammad; Rizqi Umar Al Hashfi; Izra Berakon (Universitas Airlangga, 2026)
This study aims to examine the determinants of green sukuk (GS) issuance in the Organization of Islamic Cooperation (OIC) countries by analyzing the roles of foreign direct investment (FDI), sustainable development (SD), and governance quality (GQ) in strengthening sustainable green investments. This study employs a quantitative approach using pooled cross-section and moderated regression analysis. The population includes all GS issuers, totaling 424 across five OIC countries: Bangladesh, Indonesia, Malaysia, Nigeria, and Türkiye. The data were obtained from Thomson Reuters database and analyzed using STATA 17 software. Robustness tests using the Hubber-White technique were also conducted by the researchers to strengthen the research results for each model analysis, such as the time period of investment (short- or long-term issuance). The result highlights the significance of FDI and SD in enhancing GS issuance in OIC countries. Furthermore, GQ significantly enhances the impact of FDI on both GS and SD. The model remains consistent across country-level controls. Additionally, robustness tests have confirmed that the impact of FDI and SD on GS, moderated by GQ, is robust for both short- and long-term investments. The finding suggests that OIC countries can expand GS issuance by attracting more foreign investments and strengthening sustainable development policies, especially when supported by good governance practices. Future studies are encouraged to involve a larger number of countries, include additional determinants, and conduct comparative analysis between OIC and non-OIC countries to provide broader insights into green sukuk development.